3 medals for UMP in SUKUM 2022 - Nor Salwana, Mohammad Idris (2022)
SERDANG, 27 September 2022 – Universiti Malaysia Pahang (UMP) took home two gold and one bronze medals in the 2022 Intervarsity Staff Sports (SUKUM) at Universiti Putra Malaysia (UPM) recently.